Preparo de amostras refratárias aplicando procedimentos de digestão assistidos por radiação micro-ondas e análise elementar usando ICP OES - Mello, Matheus Lima de (2020)
In this study microwave-assisted preparation procedures for decomposition of several inorganic samples and further analysis by inductively coupled plasma optical emission spectrometry (ICP OES) were developed. In order to obtain reference values, a digestion procedure using heating block with an acid mixture of concentrated HF and HNO3 was applied to achieve total digestion of the samples. This procedure was adopted for establishing reference values. In order to evaluate the feasibility of application of mild sample preparation procedures, 14, 7.0, 4.0 and 2.0 mol L-1 HNO3 and 30 % v v-1 H2O2 were utilized for digestion of inorganic samples in a single reaction chamber microwave oven. Total digestion of calcite, rock phosphate, Rh and Ru catalysts was achieved without needing of HF. Quantitative recoveries were obtained for most evaluated elements despite incomplete digestions, however, for few samples calculated recoveries were not quantitative. In order to evaluate the feasibility of HNO3 recovery from sample digests, two sub-boiling distillation experiments were proposed and involved the mixture of sample digests with technical grade HNO3 and the distillation of pre-evaporated sample digest solution. It was demonstrated that most contaminants were quantitatively removed and the recovered nitric acid provided accurate results when applied for digestion of two certified reference materials.